2023
DOI: 10.1002/iid3.967
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin alleviates imiquimod‐induced psoriasis‐like inflammation and regulates gut microbiota of mice

Abstract: BackgroundAs a polyphenolic compound originated from the food spice turmeric, curcumin (CUR) has various pharmacological effects, such as anti‐inflammatory, antioxidation, antiproliferative, and antiangiogenic activities. Psoriasis is centered on the overproduction of Th1‐ and Th2‐related cytokines (e.g., interleukin [IL]‐23, IL‐17, TNF‐α, IL‐22), which is involved in the occurrence and development of its pathogenesis. However, whether CUR is involved in the treatment of psoriasis and its specific mechanisms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…For instance, studies have shown that Streptococcus , one of the predominant genera in the gut lumen [ 32 ], was significantly elevated in the feces of psoriasis patients and mice [ 33 , 34 ]. The relative abundance of Rikenella was considerably elevated in the feces of psoriatic mice [ 35 ]. Mice with cutaneous acne induced by oleic acid showed a notable upregulation in the relative abundance of Rikenellaceae_RC9_gut_group , which was positively correlated with inflammatory factor levels [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, studies have shown that Streptococcus , one of the predominant genera in the gut lumen [ 32 ], was significantly elevated in the feces of psoriasis patients and mice [ 33 , 34 ]. The relative abundance of Rikenella was considerably elevated in the feces of psoriatic mice [ 35 ]. Mice with cutaneous acne induced by oleic acid showed a notable upregulation in the relative abundance of Rikenellaceae_RC9_gut_group , which was positively correlated with inflammatory factor levels [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenolic compounds, such as curcumin, have wide pharmacological actions, including anti-inflammatory and immunomodulatory activities, and one important mechanism is their reaction oxygen species (ROS) scavenging function [52]. The anti-psoriasis effect of curcumin is also reported [53], and the regulation of Th-17-related inflammatory factors is considered as one of the mechanisms [54]. Moreover, the relationship between the anti-psoriasis effect of GC and the molecular structure of GC needs deep exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, intragastric administration of CUR in psoriatic mice may not only result in a reduction in pro-inflammatory molecules expression (IL-6, IL-17A, IL-22, IL-23, TNF-α, and TGF-β1), but also in regulation of the gut microbiota. Recent findings suggest that CUR can promote the abundance of selected genera (i.e., Alistipes, Rikenella, and Mucispirillum) in intestinal flora, which were positively correlated with indirect anti-inflammatory activity [34].…”
Section: Curcumin and Skin Diseases 21 Psoriasismentioning
confidence: 99%